PENGEMBANGAN KEMAMPUAN LISAN BERAHASA ARAB: INTEGRASI OPERANT CONDITIONING DALAM LINGKUNGAN PEMBELAJARAN BAHASA YANG HOLISTIK - Tolak Indayati; Umar Manshur; Azilurrahman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to explore the integration of the Arabic language environment with operant conditioning strategies in improving students' speaking skills (maharah kalam). The research uses a qualitative approach with a case study design carried out at Madrasah Aliyah Nurul Jadid class XI Language Program. Data were collected through participatory observations, interviews with students and teachers, and documentation related to students' speaking activities in Arabic. The results of the study showed that the application of positive and negative reinforcement in the language environment that supported significantly increased the maharah of students' kalam, as well as corrected errors in the use of grammar. In addition, student involvement in a holistic learning environment also supports the development of students' speaking skills because this holistic learning not only includes language theory, but also pays attention to cultural aspects and contexts related to language skills.